Textbook of neural repair and rehabilitation - Selzer, Michael E. (Cambridge University Press, 2006)
In two freestanding volumes, Textbook of Neural Repair and Rehabilitation provides comprehensive coverage of the science and practice of neurological rehabilitation. This volume, Neural Repair and Plasticity, covers the basic sciences relevant to recovery of function following injury to the nervous system, reviewing anatomical and physiological plasticity in the normal CNS, mechanisms of neuronal death, axonal regeneration, stem cell biology, and neuron replacement. Edited and written by leading international authorities, it is an essential resource for neuroscientists and provides a foundation for the work of clinical rehabilitation professionals.